Ekopesantren Pondok Pesantren Annuqayah (Strategi Konservasi Lingkungan dan Penguatan Agraria pada Masyarakat Pedesaan Kabupaten Sumenep) - Nailur Ridha; Abdul Wahid (Magister’s Program in Islamic Education Postgraduate Program, Universitas Annuqayah Sumenep, 2022)
This research aims to reveal and describe: a) The views of the Annuqayah Islamic Boarding School regarding environmental conservation and agrarian strengthening in rural communities in Sumenep district; and b) Environmental conservation and agrarian strengthening strategies carried out by the Annuqayah Islamic Boarding School in rural communities in Sumenep Regency. The results of the research show that: a) Ecopesantren schools as an alternative theoretical view in environmental conservation and agrarian strengthening, including: views of ecosufism, ecotheology (scientific-religious), and eco-Islamic boarding schools. Meanwhile, the object infrastructure for environmental conservation and agrarian strengthening at the Annuqayah Islamic Boarding School is in the form of the inanimate environment (physical environment), the biological environment (biological environment), and the socio-cultural environment (community environment). b) The environmental conservation and internal strengthening strategy carried out by the Annuqayah Islamic Boarding School through the Community Service Bureau (BPM-PPA) is through developing environmental conservation and agrarian strengthening and managing the As-Salam plantation land since 2002.